Позааудиторна робота з обдарованими студентами у вищих навчальних закладах США - Новикова, Катерина (Studies in Comparative Education, 2013)
У статті розглянуто проблему організації позааудиторної роботи з обдарованими студентами у вищих навчальних закладах США, зроблено спробу розкрити сутність позааудиторної роботи у провідному американському досвіді, виділено основні види позакласних виховних заходів у вищому навчальному закладі США. В статье рассматривается проблема организации внеаудиторной работы с одаренными студентами в высших учебных заведениях США, делается попытка описать сущность передового американского опыта во внеаудиторной работе, выделяются основные виды внеклассных воспитательных мероприятий в ВУЗе США. In the article the problem of organization of the extracurricular work of the gifted students in the Higher Educational Establishments of the USA is considered. The attempt of disclosing of essence of the extracurricular work in the positive American experience is made. The importance of the «whole gifted student» development through the extracurricular involvement in the university work as a broad educational mission is denoted. The stress is made not only on the entertaining, social and enjoyment purposes of the out-of-the-class activities, but also on the gaining and improving of the academic skills of the gifted student. The importance of all the levels (individual, institutional and community) of extracurricular work to augment the gifted students’ educational experience in the Universities of the United States of America is grounded. The positive impact on the gifted students’ emotional, intellectual, social and inter-personal development with the help of such additional work is mentioned. Building and sustaining gifted community on the US diverse University campus as a student retention is accepted as one of the common goals of the gifted student pedagogical support. The main kinds of extracurricular activities in the US higher educational establishments according to the number of the types of giftedness are determined. The participation of the gifted and talented students in the out-of-the-class activities is recognized as one of the most important factors of the integral development of the personalities with exceptional abilities.